2018
DOI: 10.1186/s12957-018-1542-z
|View full text |Cite
|
Sign up to set email alerts
|

Robotic total gastrectomy with π-shaped esophagojejunostomy using a linear stapler as a novel technique

Abstract: ObjectiveTo evaluate the intraoperative and short-term postoperative outcomes of a novel robotic intracorporeal π-shaped esophagojejunostomy (EJS) after D2 total gastrectomy (TG) using the Da Vinci robotic surgical system for intracorporeal anastomosis after TG.BackgroundIntracorporeal π-shaped EJS, using a linear stapler, was recently reported for laparoscopic total gastrectomy in patients with gastric cancer. However, robotic intracorporeal π-shaped EJS using a linear stapler has not been reported. This repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In this method, gastric resection, jejunal division and common hole closure were integrated into one procedure. The di culty of hand-sewn sutures and traction of the esophagus were solved by this method [37]. Through a retrospective analysis of 143 patients, Chen et al concluded that totally laparoscopic anastomosis with π-shaped anastomosis was safe and feasible [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this method, gastric resection, jejunal division and common hole closure were integrated into one procedure. The di culty of hand-sewn sutures and traction of the esophagus were solved by this method [37]. Through a retrospective analysis of 143 patients, Chen et al concluded that totally laparoscopic anastomosis with π-shaped anastomosis was safe and feasible [18].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in total gastrectomy with high BMI patients, it is necessary to perform a larger incision than a standard minilaparotomy for extracorporeal anastomosis with increasing risk due to lack of appropriate vision or excessive traction on the viscera [ [46] , [47] , [48] ]. In order to overcome these limitations, other authors proposed to carry out laparo-assisted intracorporeal anastomosis using stapler device with the Orvil [ 49 ] or the overlap technique [ 16 , 49 , 50 ]. Despite these solutions, using stapler device is associated with increasing cost of the procedure and with higher risk of leakage due to incomplete closure at the anastomotic level.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of a circular stapler has generally been the standard for open total gastrectomy for decades, the standard for esophagojejunostomy has not yet been established in minimally invasive surgery. For this reason, several methods of reconstruction using linear staplers, circular staplers, and an orally inserted anvil have been reported in the literature [ 15 16 17 18 19 ]. In addition, several methods for splenic hilar dissection have also been described accordingly [ 32 52 53 54 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, reconstruction of minimally invasive total gastrectomy requires a more sophisticated technique than open total gastrectomy, and it may increase the risk of anastomosis-related complications [ 11 12 13 14 ]. Therefore, previous studies that investigated potential risk factors during total gastrectomy raise particular concerns regarding anastomosis-related complications [ 15 16 17 18 19 ].…”
Section: Introductionmentioning
confidence: 99%